Difference and relationship in length of the `mean` canter stride of a horse and the intermediate strides within a two stride double fence combination - Stone, C.; Berry, J.; Attwood, S. (DCA Report; Nr. 044, 2014)
It has previously been shown the intermediate jumping strides of elite horses between two stride double fence combinations differed considerably, i.e. the first intermediate stride was longer than the second; although conducted at the same velocity (Hole et al., 2001, App. Anim. Behav. Sci. 75, 317-323). The aim of this study was to determine whether the mean length of a standard canter stride seen on the long side of the school had any relationship with the intermediate jumping strides. In addition, the study sought to find out if there was a significant difference between the lengths of the two intermediate strides in non-elite horses as has been shown in elite horses previously. A random selection of horse and rider pairings (n=6) were selected with horses aged between 8-20 years, heights between 155 cm and 164 cm. The only selection criterion was that they were capable of jumping the required combination. A double fence combination of 80 cm uprights was set up, 10 m apart within an indoor school. The riders were asked to canter down the long side of the school and jump through the combination three times. This was filmed using a Sports Motion Gait Analysis camera to determine stride length and define a mean of the attempts with the take-off and two intermediate strides measured. The results showed that there was a significant difference between the standard canter stride and the intermediate jumping strides (ANOVA, P<0.001, mean standard canter = 3.05 m, mean 1st intermediate jumping stride = 4.12 m, mean 2nd intermediate jumping stride = 3.81 m). It was also found that there was a significant difference between the two intermediate jumping strides (P=0.03) with the second stride being shorter than the first. The length of canter stride values suggests that the horse`s stride lengthens considerably in the jumping phase of show jumping activities possibly causing issues relating to judging distances regarding novice built training exercises. The horses showed different intermediate stride lengths; however, all making up the set distance in the combination through landing and take-off stride changes. This suggests that the same adaptation occurs in elite and non-elite horses, which has possible implications for course design at all levels. LP: The difference between horses` stride lengths between a standard canter and between jumping combinations is considerable. An average canter stride of a horse lengthens significantly to that used when jumping. The intermediate strides between combinations of fences are to allow the horse to regain balance and momentum allowing for the next jumping effort to be tackled safely. The horse adapts its intermediate strides from that seen as a standard canter stride and the jumping stride with the second intermediate stride being shorter than the first.